2014
DOI: 10.1002/polb.23474
|View full text |Cite
|
Sign up to set email alerts
|

Stretching temperature and direction dependency of uniaxial deformation mechanism in overstretched polyethylene

Abstract: In order to elucidate microscopic deformation behavior at different locations in isotropic semicrystalline polymers, the structural evolution of a preoriented high‐density polyethylene sample during tensile deformation at different temperatures and along different directions with respect to the preorientation was investigated by means of combined in situ synchrotron small‐angle X‐ray scattering (SAXS) and wide‐angle X‐ray diffraction (WAXD) techniques. For samples stretched along preorientation, two situations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…This reduction in ultimate mechanical properties with increasing λ pre is the result of chain alignment along the MD in the melt state during the film extrusion process . A previous study by Fu et al showed that the elongation and ultimate tensile strength of pre‐oriented HDPE films increased when the angle between pre‐orientation direction and stretching direction was altered from 0° to 45° or 90°, which indicated that λ max is also dependent on the solid‐state drawing direction. Thus, the draw down or pre‐orientation ratio ought not to be chosen too high for the purpose of achieving a high ultimate mechanical performance.…”
Section: Resultsmentioning
confidence: 93%
“…This reduction in ultimate mechanical properties with increasing λ pre is the result of chain alignment along the MD in the melt state during the film extrusion process . A previous study by Fu et al showed that the elongation and ultimate tensile strength of pre‐oriented HDPE films increased when the angle between pre‐orientation direction and stretching direction was altered from 0° to 45° or 90°, which indicated that λ max is also dependent on the solid‐state drawing direction. Thus, the draw down or pre‐orientation ratio ought not to be chosen too high for the purpose of achieving a high ultimate mechanical performance.…”
Section: Resultsmentioning
confidence: 93%
“…2). It should be mentioned that a stress-induced melting [25][26][27][28] is involved in the fragmentation process as the WAXD intensity of each crystalline peak is significantly decreased in Stage IV (Fig. 3), which may be related to a decrease of the crystallinity.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%
“…From the results of long period and thickness mentioned above, it can be easily deduced that the mechanisms before and after the transition point are different. Men and coworkers 32 proposed that the increase of long period at small strain was attributed to the elongation of amorphous layers between lamellar crystals on the basis of the structural results of the stretch of HDPE strip. It can be seen from SEM results that the pre-stretched fibers are almost composed of stacked lamellar crystals (kebab crystals); furthermore, the transition points of long spacing are very close to the yield point in the stretching curves, in addition the increase rates of long period at all temperatures are almost constant before the transition point.…”
Section: Figurementioning
confidence: 99%
“…Moreover, they found that two lamellar to fibrillar transitions in the tensile deformation of high‐density polyethylene, which were followed by stress‐induced fragmentation recrystallization process. They also investigated the effect of stretching temperature on uniaxial deformation of overstretched polyethylene using in situ synchrotron SAXS. It was found that the rapid increase of long spacing of polyethylene at low strain was mainly due to the elongation of amorphous layers between lamellae when samples were stretched along preorientation.…”
Section: Introductionmentioning
confidence: 99%